Community service on marketing online training using Shopee Live for Aglaonema farmers in Depok - Lorenta In Haryanto; Dessy Iriani Putri; Syifa Astasia Utari; Prisca Nurmala Sari; Reza Firdaus; Aqila Karliyah Aziza; Deni Fadillah; Arif Muzahidin (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The Aglaonema plant is extensively traded in the Depok region and has already been promoted through various social media platforms. The primary objective of this community service initiative is to impart knowledge to farmers regarding utilizing live features on the Shopee e-commerce platform. The partners are farmers affiliated with the Aglaonema Nusantara Association, located in Depok. The programmes were conducted in August 2023 in Pasir Putih, Sawangan. The selected approaches encompassed counseling, mentoring, and practice. Practical application and support are facilitated by a team of students who create a seller account and conduct a live demonstration on the Shopee platform. Success indicators could be observed through several means, such as output analysis, pre-test and post-test assessments, and measurement of partner satisfaction. The activity mentioned above yielded several outcomes, including establishing a Shopee seller account, a notable improvement in participants' knowledge by up to 22%, and generating a partner evaluation sheet with a satisfaction score of 4.7 out of 5, denoting a high level of satisfaction. This action was effectively executed under established protocols. Nevertheless, it is imperative to sustain this endeavour to facilitate broader adoption of technology among farmers and enhance their ability to promote and sell their agricultural product effectively.